Clinical evaluation method for blue light (456 nm) protection of skin. (16th June 2020) - Jo, Hong Li; Jung, Yuchul; Suh, Byung‐Fhy; Cho, Eunbyul; Kim, Kyungtae; Kim, Eunjoo
Abstract: Background: Blue light from electronic devices enriched with a peak at 456 nm affects circadian rhythm and antioxidant balance of skin, necessitating the study of photoprotection against the 456‐nm blue light. Aims: This study aims to report that blue light (456 nm) can cause skin pigmentation and proposes a new clinical evaluation method for blue light (456 nm) protection based on the skin pigmentation level. Patients/Methods: We developed a clinical device (ABC device TM ) that emits blue light (peak = 456 nm). Based on the minimal persistent pigment darkening dose (MPPD) determined from visual evaluation and melanin index measurements, we proposed the "protection grade of blue light (PB)" guideline to assess the protective ability of skin against blue light. Results: Human skin irradiated with blue light (456 nm) showed a light dose‐dependent degree of pigmentation. The MPPD on unprotected and protected skin was 135 J/cm 2 or 180 J/cm 2 and 135‐225 J/cm 2, respectively. The ABC device ™ and the proposed clinical method were used to test the four blue light blocking assessments of TiO2 . Consequently, the inorganic filter with TiO2 effectively blocked the blue light (456 nm). The AP product demonstrated the ability to block blue light by 1.15 times (PB = 1.15), which significantly lowered the melanin index of the skin after irradiation as compared to that of the unprotected skin ( P  < .001). Conclusion: We propose an objective clinical evaluation method for blue light protection. This study elucidates the properties of blue light blockers for customers suffering from blue light pollution.